Chapter Afterword. Notes on Rereading and Re-enacting "China" - Tarantino, Giovanni (Connessioni. Studies in Transcultural History, 2022)
In Europe, the historical representation and narration of China and the Orient more in general from an outsider's point of view has conjured up an exotic and a-historical image of a poetical, mystical and refined civilization. In Walpole's Britain, for example, "the argument from the Chinese"-namely, the admiration for a prosperous and densely populated kingdom which did not belong to a single faith-was frequently used in religious disputes when claiming a wider or more coherent policy of tolerance or seeking to cut down the prerogatives of the clerical hierarchies. This chapter explores further Western uses of "the argument from the Chinese" in modern times and through different media (Antonioni; Yanne; Martin).